An Updated Global Species Diversity and Phylogeny in the Forest Pathogenic Genus Heterobasidion (Basidiomycota, Russulales) - Yuan, Yuan; Chen, Jia-Jia; Korhonen, Kari; Martin, Francis; Dai, Yu-Cheng (Frontiers in Microbiology, 2021)
Heterobasidion species are amongst the most intensively studied polypores because several species are aggressive white rot pathogens of managed coniferous forests mainly in Europe and North America. In the present study, both morphological and multilocus phylogenetic analyses were carried out on Heterobasidion samples from Asia, Oceania, Europe and North America. Three new taxa were found, i.e., H. armandii, H. subinsulare and H. subparviporum are from Asia and are described as new species. Heterobasidion ecrustosum is treated as a synonym of H. insulare. So far, six taxa in the H. annosum species complex are recognized. H. abietinum, H. annosum and H. parviporum occur in Europe, H. irregulare, and H. occidentale in North America, and H. subparviporum in East Asia. The North American H. irregulare was introduced to Italy during the Second World War. Species in the H. annosum complex are pathogens of coniferous trees, except H. subparviporum that seems to be a saprotroph. Ten species are found in the H. insulare species complex, all of them are saprotrophs. The pathogenic species are distributed in Europe and North America; the Asian countries should consider the European and North American species as entry plant quarantine fungi. Parallelly, European countries should consider the American H. occidentale and H. irregulare as entry plant quarantine fungi although the latter species is already in Italy, while North America should treat H. abietinum, H. annosum s.s. and H. parviporum as entry plant quarantine fungi. Eight Heterobasidion species found in the Himalayas suggest that the ancestral Heterobasidion species may have occurred in Asia.